Salmonella infections in Antarctic fauna and island populations of wildlife exposed to human activities in coastal areas of Australia - Iveson, J.; Shellam, G.; Bradshaw, S.; Smith, D.; Mackenzie, John; Mofflin, R. (Cambridge University Press, 2009)
Salmonella infections in Antarctic wildlife were first reported in 1970 and in a search for evidence linking isolations with exposure to human activities, a comparison was made of serovars reported from marine fauna in the Antarctic region from 1982-2004 with those from marine mammals in the Northern hemisphere. This revealed that 10 (83%) Salmonella enterica serovars isolated from Antarctic penguins and seals were classifiable in high-frequency (HF) quotients for serovars prevalent in humans and domesticated animals. In Australia, 16 (90%) HF serovars were isolated from marine birds and mammals compared with 12 (86%) HF serovars reported from marine mammals in the Northern hemisphere. In Western Australia, HF serovars from marine species were also recorded in humans, livestock, mussels, effluents and island populations of wildlife in urban coastal areas. Low-frequency S. enterica serovars were rarely detected in humans and not detected in seagulls or marine species. The isolation of S. Enteritidis phage type 4 (PT4), PT8 and PT23 strains from Adélie penguins and a diversity of HF serovars reported from marine fauna in the Antarctic region and coastal areas of Australia, signal the possibility of transient serovars and endemic Salmonella strains recycling back to humans from southern latitudes in marine foodstuffs and feed ingredients. © 2008 Cambridge University Press.